The Association between Emotional Intelligence and Academic Adaptation among a Sample of Gifted Students in the Intermediate and Secondary Schools in Jeddah (Journal Of Educational and Psychological Researches, 2023)
This study aims to examine the relationship between emotional intelligence and academic adaptation among a sample of gifted students in intermediate and high schools in Jeddah, Saudi Arabia. The study also seeks to examine the differences between group means in emotional intelligence and academic adaptation due to demographic variables (gender and school level). In addition, the study aims to examine the role of emotional intelligence in predicting the level of academic adaptation. The researcher performed the descriptive, correlational, predictive, and comparative approaches to collect the data from a sample comprised of (309) gifted students using the emotional intelligence scale developed by Bar-on (2000), which was translated by the researcher, and the academic adaptation scale developed by Alabdalat (2008). The study findings showed a medium level of emotional intelligence and academic adaptation among the study sample, and no correlation was found between emotional intelligence and academic adaptation. In addition, the findings revealed statistically significant differences in emotional intelligence between males and females in favor of females, and between students’ school level in favor of secondary school. Moreover, there are statistically significant differences in academic adaptation between males and females in favor of males, and no differences were found due to school level. The findings also indicated that emotional intelligence had no role in predicting the level of academic adaptation. In light of the study results, the researcher recommends developing appropriate counseling programs to improve gifted students’ emotional intelligence, which may play a positive role in their academic adaptation.